A Novel Hydrogen Sulfide Donor Reduces Pilocarpine-Induced Status Epilepticus and Regulates Microglial Inflammatory Profile - Liu, Zhongrui; Zhu, Ziting; He, Yan; Kang, Qiyun; Li, Fei; Zhang, Wenlong; He, Yuehua; Lin, Yuwan; Huang, Baoyi; Mo, Mingshu; Xu, Pingyi; Zhu, Xiaoqin (Frontiers in Cellular Neuroscience, 2021)
There is still a lack of effective therapeutic drugs for epilepsy, although it is one of the most common neurologic disorders. Recently, we synthesized a novel hydrogen sulfide (H2S) donor, which is found to effectively reduce seizures in animal models. But it remains to be determined for its mechanism. In the present study, we found that the novel H2S donor could reduce pilocarpine-induced seizures in mice. It alleviated the epileptic behavior, the hippocampal EEG activity of seizures and the damage of hippocampal neurons in status epilepticus mice. In addition, the novel H2S donor could reduces microglial inflammatory response. It not only reduced the up-regulation of pro-inflammatory markers (iNOS and COX2) in status epilepticus mice, but also increased the levels of microglial anti-inflammatory marker Arg-1. In lipopolysaccharide treated microglia BV2 cells, administration of the H2S donor also significantly reduced the lipopolysaccharide-induced up-regulation of the expression of the pro-inflammatory markers and increased the expression of the anti-inflammatory markers. Thus, the novel H2S donor regulates microglial inflammatory profile in status epilepticus mice and in vitro. These results suggested that the novel H2S donor reduced seizures by regulating microglial inflammatory profile, which may be a novel mechanism and potential therapeutic strategy of the H2S donor anti- seizures.